Reactive morphological changes of rat’s hearts with experimental undifferentiated dysplasia of connective tissue - Hryhorieva, O. A.; Guminskiy, Yu. Yo.; Chernyavskiy, A. V.; Tavrog, M. L.; Zinich, O. L.; Григор'єва, Олена Анатоліївна; Чернявський, Артур Валерійович; Таврог, Маріанна Львівна; Зінич, Олена Леонідівна (My University, 2020)
In modern literature, there are sufficient data concerning clinical manifestations of connective tissue dysplasia, its diagnosis, principles of correction, but works devoted to factors that lead to dysplasia, and morphological manifestations of this condition are insufficient. The aim: to establish a reactive morphological changes of the heart of rats with an experimental undifferentiated dysplasia of connective tissue.